Cortical thickness and subcortical volume abnormalities in male crack-cocaine users. (30th April 2021) - Bittencourt, Augusto Martins Lucas; Bampi, Vinicius Faccin; Sommer, Rafael Canani; Schaker, Vanessa; Juruena, Mario Francisco Pereira; Soder, Ricardo Bernardi; Franco, Alexandre Rosa; Sanvicente-Vieira, Breno; Grassi-Oliveira, Rodrigo; Ferreira, Pedro Eugenio Mazzucchi Santana
Highlights: Crack-cocaine users showed lower cortical thickness than healthy controls. We found a negative correlation between crack years of use and cortical thickness. There is a lack of neuroimaging studies dedicated to crack-cocaine addiction. Abstract: Crack-cocaine offers a higher risk of abuse than intranasal and intravenous use of cocaine. Yet, current treatments remain disappointing and our understanding of the mechanism of crack-cocaine neurotoxicity is still incomplete. Magnetic resonance images studies on brain changes of crack-cocaine addicts show divergent data. The present study investigated gray matter (GM) abnormalities in crack-cocaine dependents ( n = 18) compared to healthy controls ( n = 17). MRI data was analysed using FreeSurfer and voxel-based morphometry (VBM). FreeSurfer analysis showed that CD had decreased cortical thickness (CT) in the left inferior temporal cortex (lTC), left orbitofrontal cortex (lOFC) and left rostro frontal cortex (lRFC), enlargement in left inferior lateral ventricle, and smaller GM volume in right hippocampus and right ventral diencephalon. VBM analysis showed that CD had significantly decreased GM volume in left Putamen and left nucleus accumbens. Furthermore, we found a negative correlation between duration of crack-cocaine use and lTC CT. These results provide compelling evidence for GM abnormalities in CD and also suggest that duration of crack-cocaine use may be associated with CT alterations.